2017
DOI: 10.1039/c7ra04074a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vasodilator drugs through microwave spectroscopy of Au NP colorimetric probes using a microwave metallic photonic crystal-inspired resonant probe

Abstract: A low-cost, time-effective and easy-to-use novel analytical technique incorporating microwave spectroscopy of unmodified gold nanoparticles for the detection of selected vasodilator drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has been observed that the consumption of pharmaceutical products by living organisms and their disposal in the environment has increased gradually. Disposal of unused medication into the environment is considered to be the major source for the occurrence of pharmaceutical waste in the environment. Owing to the negative potential effects that they cause to the environment, special attention has been focused for the estimation of such residues. In this regard, Zhang et al reported the matrix effects for the evaluation of various pharmaceutical residues in seawater using UHPLC or CID MS-MS methods .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the consumption of pharmaceutical products by living organisms and their disposal in the environment has increased gradually. Disposal of unused medication into the environment is considered to be the major source for the occurrence of pharmaceutical waste in the environment. Owing to the negative potential effects that they cause to the environment, special attention has been focused for the estimation of such residues. In this regard, Zhang et al reported the matrix effects for the evaluation of various pharmaceutical residues in seawater using UHPLC or CID MS-MS methods .…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Lad et al detected two vasodilator drugs, i.e., amlodipine besylate and minoxidil, using hybrid gold nanoparticles. They proposed aggregation of gold nanoparticles upon binding with drug molecules as the binding mechanism . In other study, silica-coated reverse-phase column chromatography was employed by Paull et al for the determination of pharmaceutical residues in environmental samples .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation